Competitive exchange of Cr (III) sorption on macroporous Amberlyst.15 (H). (18th January 2017) - Shah, Khizar Hussain; Mustafa, Syed; Waseem, Muhammad; Hamayun, Muhammad; Shah, Faheem; Rehman, Wajid; Khan, Abdur Rahman
Abstract: In the present investigation, the kinetics of Cr (III), Al (III) and Ca (II) ions sorption onto macroporous Amberlyst.15 (H + ) from an equimolar mixture of metal ions is studied at different temperatures (293–333 K). The equilibrium time for the competitive sorption is found to be dependent on the temperature in case of Cr (III) ions while independent for Ca (II) and Al (III) ion exchange. The exchange capacities are observed to follow the order: Ca (II)  >  Cr (III)  >  Al (III) in the mixed metal systems, which can be co-related with hydration energy of the corresponding cations. The kinetics data is analyzed by Boyd Film diffusion and simplified Reichenberg particle diffusion models. The kinetic and activation parameters have also been evaluated from Arrhenius and Eyring equations and their significance discussed. The values of activation energies for the competitive sorption are observed to be 16.61, 6.96 and 8.42 kJ mol −1 for Cr (III), Al (III) and Ca (II) respectively. The thermodynamic activation parameters indicated that the ion exchange mechanism of Cr (III), Al (III) and Ca (II) ions onto the Amberlyst.15 (H + ) is entropy driven in nature.